2012
DOI: 10.2298/hemind111111002r
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging activity, total phenolic and flavonoid contents of mulberry (Morus spp. L., Moraceae) extracts

Abstract: Mulberry (Morus spp. L., Moraceae) fruits, leaves, bark and branch have been used in traditional medicine as diuretic, hypoglycemic and hypotensive. The mechanism of their effects is correlated with the content of active components. Objective of this work was to evaluate and compare antioxidant properties of different extracts of two Morus species growing in Serbia: Morus alba L. (white mulberry) and Morus nigra L. (black mulberry). Potential antioxidant activity, content of antioxidant compounds (phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 28 publications
9
53
4
5
Order By: Relevance
“…As in other studies (Arabshahi-Delouee & Urooj, 2007;Radojkovic et al, 2012), results showed that mulberry is very different to other fruits (different PCA group). PCA also confirmed the scientific validity of the pH-differential method for TAC quantification; monomeric anthocyanins, indeed, undergo a reversible structural transformation as a function of pH (colored oxonium form at pH 1.0 and colorless hemiketal form at pH 4.5): PCA graph confirmed the relationship between monomeric anthocyanins and pH showing the anti-correlation between the content of total anthocyanins and the pH-values.…”
Section: Discussionsupporting
confidence: 76%
“…As in other studies (Arabshahi-Delouee & Urooj, 2007;Radojkovic et al, 2012), results showed that mulberry is very different to other fruits (different PCA group). PCA also confirmed the scientific validity of the pH-differential method for TAC quantification; monomeric anthocyanins, indeed, undergo a reversible structural transformation as a function of pH (colored oxonium form at pH 1.0 and colorless hemiketal form at pH 4.5): PCA graph confirmed the relationship between monomeric anthocyanins and pH showing the anti-correlation between the content of total anthocyanins and the pH-values.…”
Section: Discussionsupporting
confidence: 76%
“…Memon et al (2010) reported for the berries of white mulberry that chlorogenic acid was the phenolic compound with the richest content. However, Radojković et al (2012) stated that rutin was the main phenolic compound for white (43.5 mg 100 g −1 ) and black (72.6 mg 100 g −1 ) mulberry species. It is clear that the amount of phenolic content in mulberries varied according to species, genotypes, plant age, cultural and growing conditions, extraction methods, etc.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Many authors have investigated the phytochemical content of the mulberries grown in different parts of the world including Turkey, Serbia, Slovenia, Spain, Poland, and Pakistan (Koyuncu 2004;Zadernowski et al 2005;Gungor and Sengul 2008;Ozgen et al 2009;Memon et al 2010;Gundogdu et al 2011;Arfan et al 2012;Mahmood et al 2012;Mikulic-Petkovsek et al 2012;Radojković, et al 2012;Sanchez et al 2014). However, detailed data regarding the sugars, organic acids, and phenolic compounds of the white and black mulberries are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] There are several compounds extracted from black mulberry that possesses antibacterial activity, including 1-arylbenzofuran (Moracin M), stilbenoid oxyresveratrol, morusin, and kuwanon C. [9,10] Due to these constituents, the black mulberry (M. nigra) has potential as an anti-acne agent for facial skin treatment.…”
Section: National Journal Of Physiology Pharmacy and Pharmacology 98mentioning
confidence: 99%